Hallux Valgus Correction Using a Novel 3D Printed Plate: Retrospective Case Series with Two Year Follow-Up Data: Surgical Technique Guide and Outcomes. Issue 4 (16th October 2019) - Brohard, Justin; Callahan, Ryan; Lin, Jason
Category: Bunion Introduction/Purpose: Over 130 techniques have been described for the treatment of hallux valgus, ranging from bunionectomies, osteotomies, and arthrodesis. Modern attempts at bunion correction with less invasive joint sparing approaches, such as suture-button techniques, have introduced additional complications like second metatarsal fracture. Suture fixation techniques have evolved in an attempt to avoid these complications. We present our results, with up to 26 months of radiographic follow up including initial correction and complications, with a novel device which utilizes a 3D printed titanium plate on the lateral cortex of the second metatarsal without bony violation, and reduces the 1-2 intermetatarsal angle using suture tape passed through drill holes in the first metatarsal with PEEK interference screw fixation. Methods: This study includes 33 feet in 31 patients. A single board certified and fellowship trained orthopedic foot and ankle surgeon performed all operations over the course of 18 months at a single institution. He utilized a dual incision approach and followed previously described surgical technique for the application of the device. We retrospectively reviewed radiographs including pre-operative AP, lateral, and oblique images, along with another set at the two and six week post operative periods, and another at the last available follow up visit. Using standard technique we measured the 1-2 intermetatarsal angle (IMA), as well as the hallux valgus angle (HVA), which were used as the primary outcomes. Chart review was performed to determine patient satisfaction with the outcome. All secondary procedures and complications were recorded based on the chart review and radiographs. Results: Average radiographic follow up was 15 months. The average initial HVA was 31.4º and IMA was 16.0º. Two-week average HVA was 11.3º and IMA was 7.1º. At six weeks, weight-bearing radiographs showed an average HVA 14.5º and IMA 8.2º. Final radiographic measurements, accounting for either the latest available image or the final image prior to revision, showed average HVA of 24.3º and IMA of 13.7º. Six patients had revision for recurrence or fracture. One underwent removal of symptomatic hardware. Seventeen patients had at least mild radiographic recurrence, without revision. Two patients had an intraoperative fracture of the first metatarsal, and one had an intraoperative fracture of the second metatarsal shaft. There were no infections or wound healing issues. Conclusion: Although this device allows a minimally invasive hallux valgus correction, and provides a powerful initial correction with little bony manipulation, results presented in this study suggest a high rate of radiographic recurrence, and relatively high rates of intra-operative complication, post-operative complication, and revision surgery. We found that more severe deformity had a higher rate of recurrence, suggesting it may be more beneficial in mild deformity, but even in many of these patients we found recurrence and other complications. As a result, this technique has since been abandoned at our local institution with the last procedure being performed in 2016.